Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1161/jaha.116.004421
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin Elicits Potent Constrictor Actions via Chemokine‐Like Receptor 1 (CMKLR1), not G‐Protein‐Coupled Receptor 1 (GPR1), in Human and Rat Vasculature

Abstract: BackgroundCirculating levels of chemerin are significantly higher in hypertensive patients and positively correlate with blood pressure. Chemerin activates chemokine‐like receptor 1 (CMKLR1 or ChemR23) and is proposed to activate the “orphan” G‐protein‐coupled receptor 1 (GPR1), which has been linked with hypertension. Our aim was to localize chemerin, CMKLR1, and GPR1 in the human vasculature and determine whether 1 or both of these receptors mediate vasoconstriction.Methods and ResultsUsing immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 53 publications
3
76
0
Order By: Relevance
“…To evaluate the impact of the cMKlr1 agonist, chemerin-9, on PdM, peritoneal injections of phosphate buffer solution (PBS, 200 µl, control group, n=8) or chemerin-9 (4 µg in 200 µl PBS, n=8) or were performed every day for 42 days, as previously described (17). Blood samples were collected at day 0 and 42.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the impact of the cMKlr1 agonist, chemerin-9, on PdM, peritoneal injections of phosphate buffer solution (PBS, 200 µl, control group, n=8) or chemerin-9 (4 µg in 200 µl PBS, n=8) or were performed every day for 42 days, as previously described (17). Blood samples were collected at day 0 and 42.…”
Section: Methodsmentioning
confidence: 99%
“…In this line, several studies have shown that chemerin is able to promote contractility in blood vessels, including the pulmonary artery, aorta, and superior mesenteric artery in rats and the human saphenous vein [ 146 , 147 , 148 , 149 , 150 ]. It has also been demonstrated that chemerin promotes the increase of blood pressure in rats and mice [ 149 , 151 , 152 , 153 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…In this line, several studies have shown that chemerin is able to promote contractility in blood vessels, including the pulmonary artery, aorta, and superior mesenteric artery in rats and the human saphenous vein [ 146 , 147 , 148 , 149 , 150 ]. It has also been demonstrated that chemerin promotes the increase of blood pressure in rats and mice [ 149 , 151 , 152 , 153 ]. These results are consistent with the presence of increased circulating levels of chemerin in patients with hypertension [ 90 , 125 , 154 , 155 ], where chemerin correlates with inflammatory markers such as TNFα, CRP, and IL-6; metabolic syndrome; and adipose tissue accumulation [ 90 , 125 , 154 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…In addition to activating CMKLR1, human chemerin21 – 157, C9, and C13 have also been found to activate orphan receptor, G protein – coupled receptor 1 (GPR1). This pairing was initially discovered due to the high sequence identity between GPR1 and CMKLR1 ( Barnea et al, 2008 ) and has subsequently been independently confirmed ( Southern et al, 2013 ; Rourke et al, 2014 ; Kennedy et al, 2016 ).…”
Section: Introductionmentioning
confidence: 85%